Improved Local Anesthesia at Inflamed Tissue Using the Association of Articaine and Copaiba Oil in Avocado Butter Nanostructured Lipid Carriers - Gustavo Henrique Rodrigues da Silva; Julia Borges Paes Lemes; Gabriela Geronimo; Fabíola Vieira de Carvalho; Talita Cesarim Mendonça; Kauê Franco Malange; Fernando Freitas de Lima; Márcia Cristina Breitkreitz; Carlos Amilcar Parada; Teresa Dalla Costa; Eneida de Paula (MDPI AG, 2023)
Unsuccessful anesthesia often occurs under an inflammatory tissue environment, making dentistry treatment extremely painful and challenging. Articaine (ATC) is a local anesthetic used at high (4%) concentrations. Since nanopharmaceutical formulations may improve the pharmacokinetics and pharmacodynamics of drugs, we encapsulated ATC in nanostructured lipid carriers (NLCs) aiming to increase the anesthetic effect on the inflamed tissue. Moreover, the lipid nanoparticles were prepared with natural lipids (copaiba (Copaifera langsdorffii) oil and avocado (Persia gratissima) butter) that added functional activity to the nanosystem. NLC-CO-A particles (~217 nm) showed an amorphous lipid core structure according to DSC and XDR. In an inflammatory pain model induced by λ-carrageenan in rats, NLC-CO-A improved (30%) the anesthetic efficacy and prolonged anesthesia (3 h) in relation to free ATC. In a PGE2-induced pain model, the natural lipid formulation significantly reduced (~20%) the mechanical pain when compared to synthetic lipid NLC. Opioid receptors were involved in the detected analgesia effect since their blockage resulted in pain restoration. The pharmacokinetic evaluation of the inflamed tissue showed that NLC-CO-A decreased tissue ATC elimination rate (ke) by half and doubled ATC's half-life. These results present NLC-CO-A as an innovative system to break the impasse of anesthesia failure in inflamed tissue by preventing ATC accelerated systemic removal by the inflammatory process and improving anesthesia by its association with copaiba oil.